Dovbnia N.P., Bondarenko L.M., Bobir D.V, Korenjuk R.A. Update supplemented by calculations brake with gain. - Довбня, Н.П.; Бондаренко, Л.М.; Бобырь, Д.В.; Коренюк, Р.А. (Problems of Tribology, 2014)
Analysis of the calculations for the refinement of braking torque in the parking lot and moving the rolling resistance balls during the thrust disk to the following conclusions and recommendations:- influence rolling resistance ball resting on the inclined plane of the grooves on the brakes with increasing values of spacing effort and slight braking torque (for example, received tenths of a percent);- range of friction values for the received external and internal radii found by the proposed method from the condition that the work of friction with respect to the radius of the friction is not very different from their values obtained as the radius of the equivalent all the elementary forces of friction or as arithmetic mean of the radii;- these calculation results are valid only for the assumed size and strength on the rod cylinder, and in the general case, the calculation should be performed by the proposed method